Wholistic and Ethical: Social Inclusion with Indigenous Peoples - Absolon, Kathleen E. (Social Inclusion, 2016)
This paper begins with a poem and is inclusive of my voice as Anishinaabekwe (Ojibway woman) and is authored from my spirit, heart, mind and body. The idea of social inclusion and Indigenous peoples leave more to the imagination and vision than what is the reality and actuality in Canada. This article begins with my location followed with skepticism and hope. Skepticism deals with the exclusion of Indigenous peoples since colonial contact and the subsequent challenges and impacts. Hope begins to affirm the possibilities, strengths and Indigenous knowledge that guides wholistic cultural frameworks and ethics of social inclusion. A wholistic cultural framework is presented; guided by seven sacred teachings and from each element thoughts for consideration are guided by Indigenous values and principles. From each element this paper presents a wholistic and ethical perspective in approaching social inclusion and Indigenous peoples. (author's abstract)